Oogenesis of Hematophagous Midge Forcipomyia taiwana (Diptera: Ceratopogonidae) and Nuage Localization of Vasa in Germline Cells - Wang, Szu-Chieh; Ching, Yung-Hao; Krishnaraj, Preethi; Chen, Guan-Yu; Radhakrishnan, Anna Shiny; Lee, Hsien-Min; Tu, Wu-Chun; Lin, Ming-Der (Insects (Basel, Switzerland), 2020)
Forcipomyia taiwana is an irritating hematophagous midge that preferentially attacks humans and affects leisure industries in Taiwan. Understanding the female reproductive biology of such pests would facilitate the development of pest control strategies. However, knowledge about oogenesis in the genus Forcipomyia is unavailable. Accordingly, we examined the ovariole structure and features of oogenesis in terms of the oocyte and the nurse cell. After being blood-fed, we observed a high degree of gonotrophic harmony—the synchronization of developing follicles. The follicle of the F. taiwana has only one nurse cell connected to the oocyte, which is distinct among hematophagous midges. In the nurse cell, we identified the perinuclear localization of the germline marker, Vasa. The Vasa localization is reminiscent of the nuclear envelope-associated nuage observed by electron microscopy. To determine whether F. taiwana Vasa (FtVasa) is an authentic nuage component, we produced transgenic flies expressing FtVasa in the female germline and proved that FtVasa was able to be localized to Drosophila nuage. By characterizing the oogenesis and Vasa expression in the germline cells of F. taiwana, this study extends knowledge about the female reproductive biology of hematophagous midges.